Synthesis of 3-Phenylisoindolinones by Reaction of 2-Carboxybenzophenone and 2-Methoxycarbonylbenzophenone with Ureas in Formic Acid; Russian Journal of Organic Chemistry; Vol. 39, iss. 8 - Bakibaev A. A. Abdigali Abdimanapovich (2003, 2003)
Title screen